Editorial (American Journal of Islam and Society, 2008)
One of the paradoxes facing conservative Muslims in North America is that whiletheir apologetic literature stresses “Islam as justice” – that justice is the paradigmaticQur’anic virtue after piety – in the eyes of the general public the progressiveMuslims have claimed the mantle of justice. This is a shame, since conservative ortraditionalMuslims are held to be generally unjust, whereas, as followers of Islam’straditional teachings, they ought to be at the forefront of the struggle for social andeconomic justice. There are two dimensions to this perception: one is externallygenerated and constitutes a very real threat to NorthAmerica’sMuslims; the secondone is internally generated and constitutes a significant barrier to Islam’s positivereception by NorthAmerican society.It is not an original statement to note that Islam’s general public image is bad.Many scholars, among them Edward Said, Karim Karim, and Jack Shaheen, havedemonstrated time and again how the western legacy of Orientalism moved out ofthe academy and into the secular media with the rise of the film and print mediaindustries. Such post-9/11 experts as Mahmoud Hamdani have noted the refining ofthis image into a “good Muslim”/“bad Muslim” dichotomy. The secular or “moderate”Muslims receive the accolade of the “good Muslims,” while traditional andconservativeMuslims are the “badMuslims.” Efforts by Daniel Pipes and other neoconservativewriters to ensure that the general public and policy makers do not distinguishbetween moderate conservatives and those who endorse violence to achievetheir goals have, unfortunately, been very successful.The Clarion Fund’s mass mailing of the DVD “Radical Obsession” to 28 millionhouseholds in September 2008 clarifies the enormous power behind such neoconservativegoals. “Radical Obsession,” which purports to be only about jihadism,manages through its imagery to connect allMuslims to violence.An excellently executedpiece of propaganda, it will likely have the desired goal: creating fear in thegeneral public’s mind about conservative Muslims. (Secular and progressiveMuslims will also suffer in the long run, as the general public will not be able to distinguishbetween a secular and a non-secular Muslim, which is why the supportvoiced by some of these Muslims vis-à-vis the DVD is disappointing, to say the least.) ...